Microbiological profile of early-onset neonatal sepsis in a tertiary care hospital in South India - Gupta, Ankur; Philip, Prijo; Madhava, Kamath K (Indian Journal of Child Health, 2016)
Aims: To identify the microbiological profile of neonatal sepsis and antibiotic sensitivity patterns of various isolates in the Newborn Intensive Care Unit at a Tertiary Care Hospital in Karnataka. Materials and Methods: In this retrospective study, the laboratory data of primary blood culture reports of 240 neonates admitted with clinical suspicion of early-onset sepsis, from April 2014 to March 2016, were analyzed. Results: Total 240 samples were received during the study period, of which 40, (16%) were found to be positive. Out of these, 18 (7.5%), 18 (7.5%), and 4 (1%) had Gram-positive, Gram-negative, and Candida infection, respectively. The most common organism noted among Gram-positive isolates was Staphylococcus aureus (22.5%), followed by coagulase-negative staphylococci (12.5%) and Enterococcus (10%). Among Gram-negative isolates, Acinetobacter was the most commonly implicated organism (20%), followed by Klebsiella pneumoniae (12.5%), Escherichia coli (7.5%), and Pseudomonas aeruginosa (5%). Conclusion: This study emphasizes the need for close observation to be carried out at regular intervals to describe the various pathogens causing early-onset neonatal sepsis and their ever changing antibiotic sensitivity pattern which will provide useful data to guide practice and policies on rational use of antibiotics.